Fate of soil organic carbon and polycyclic aromatic hydrocarbons in a vineyard soil treated with biochar - Rombolà, Alessandro G.; Meredith, Will; Baronti, Silvia; Snape, Colin E.; Genesio, Lorenzo; Vaccari, Francesco Primo; Miglietta, Franco; Fabbri, Daniele (ACS Publications, 2015)
The effect of biochar addition on the levels of black carbon (BC) and polcyclic aromatic hydrocarbons (PAHs) in a vineyard soil in central Italy was investigated within a two year period. Hydropyrolysis (HyPy) was used to determine the contents of BC (BCHyPy) in the amended and control soils while the hydrocarbon composition of the semi-labile (non-BCHyPy) fraction released by HyPy was determined by gas chromatography-mass spectrometry, together with the solvent-extractable PAHs. The concentrations of these three polycyclic aromatic carbon reservoirs, changed and impacted differently on the soil organic carbon over the period of the trial. The addition of biochar (33 ton dry biochar ha-1) gave rise to a sharp increase in soil organic carbon which could be accounted for by an increase of BCHyPy. Over time, the concentration of BCHyPy decreased significantly from 36 to 23 mg g-1, and as a carbon percentage from 79% to 61%. No clear time trends were observed for the non-BCHyPy PAHs varying from 39 to 34 µg g-1 in treated soils, not significantly different from control soils. However, the concentrations of extractable PAHs increased markedly in the amended soils, and decreased with time from 153 to 78 ng g-1 remaining always higher than those in untreated soil. The extent of the BCHyPy loss was more compatible with physical rather than chemical processes.